Molecular dynamics simulations reveal proton transfer pathways in cytochrome C-dependent nitric oxide reductase. - Andrei V Pisliakov; Tomoya Hino; Yoshitsugu Shiro; Yuji Sugita (PLoS Computational Biology)
Nitric oxide reductases (NORs) are membrane proteins that catalyze the reduction of nitric oxide (NO) to nitrous oxide (N(2)O), which is a critical step of the nitrate respiration process in denitrifying bacteria. Using the recently determined first crystal structure of the cytochrome c-dependent NOR (cNOR) [Hino T, Matsumoto Y, Nagano S, Sugimoto H, Fukumori Y, et al. (2010) Structural basis of biological N2O generation by bacterial nitric oxide reductase. Science 330: 1666-70.], we performed extensive all-atom molecular dynamics (MD) simulations of cNOR within an explicit membrane/solvent environment to fully characterize water distribution and dynamics as well as hydrogen-bonded networks inside the protein, yielding the atomic details of functionally important proton channels. Simulations reveal two possible proton transfer pathways leading from the periplasm to the active site, while no pathways from the cytoplasmic side were found, consistently with the experimental observations that cNOR is not a proton pump. One of the pathways, which was newly identified in the MD simulation, is blocked in the crystal structure and requires small structural rearrangements to allow for water channel formation. That pathway is equivalent to the functional periplasmic cavity postulated in cbb(3) oxidase, which illustrates that the two enzymes share some elements of the proton transfer mechanisms and confirms a close evolutionary relation between NORs and C-type oxidases. Several mechanisms of the critical proton transfer steps near the catalytic center are proposed.